2022
DOI: 10.1371/journal.pone.0262498
|View full text |Cite
|
Sign up to set email alerts
|

Changes in speech, language and swallowing services during the Covid-19 pandemic: The perspective of speech-language pathologists in Saudi Arabia

Abstract: Purpose The study aimed to investigate changes in the role of speech-language pathologists (SLPs) during the COVID-19 pandemic in Saudi Arabia. It also assessed the SLPs’ perceptions of delivering services using telehealth as a part of their everyday clinical practice before and during the COVID-19 pandemic. Method SLPs in Saudi Arabia were invited to complete a web-based survey covering questions related to changes to the role of SLPs during the COVID-19 pandemic, changes in the ways speech services are del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…communication). Across the world, matching our findings, there is a suggestion that remote services will remain (Al Awaji et al, 2022;Campbell & Goldstein, 2022) with the reported benefits of hybrid services emerging (Terrell et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…communication). Across the world, matching our findings, there is a suggestion that remote services will remain (Al Awaji et al, 2022;Campbell & Goldstein, 2022) with the reported benefits of hybrid services emerging (Terrell et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…For families who were able to use telehealth, the increased links between SLTs and parents were seen as a strong positive compared to typical school-based practice where family contact was limited. The RCSLT (2020); RCSLT (2022) likewise found school closures and the move to telehealth had some positive impacts, including greater contact with parents, and reflects findings in other UK paediatric services (Royal College of Speech & Language Therapists (RCSLT), 2022) and SLT services overseas (Al Awaji et al, 2022;Eguia & Capio, 2022). It should be noted that not all our participants reported their telehealth access and skills improved, though more than the wider RCSLT member survey (54% increase in skills) (Royal College of Speech & Language Therapists, 2020).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, other researchers in an exploratory study reported an urgent need to increase awareness of telemedicine among dental healthcare professionals [ 32 ]. It has also been reported that the use of and access to regular dental care are limited, and patients mostly visit the dentist for procedures [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The unique strategic benefits of language are manifested by promoting the integration of different civilizations and resolving cultural conflicts. The definition of language service is that, as a subject of behavior, it provides a helping hand to others and society through words, showing humanism and communication characteristics [3]. Content or form is expressed through its words, indicating that it has the characteristics of knowledge and tools.…”
Section: Introductionmentioning
confidence: 99%